ANALISIS AKULTURASI KEBUDAYAAN ANTARA MASYARAKAT TRANSMIGRAN DENGAN MASYARAKAT LOKAL - Firdaus, Lukman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â AbstractThe objective of this research was to know the Acculturation of Culture between Transmigrant Communities with Local Communities in Desa Tunggal Bhakti Kecamatan Kembayan Â Kabupaten Sanggau. This research uses descriptive qualitative approach method. The techniques of data collection observation, interviews, and documentation. The research instruments were the directive of observation, directive of interview, and the documentation tools. The research showed the Acculturation in the form of social organization has been mixed, because social organization carries the name of an ethnic but its membership has mixed up. Caused by several factors namely marriage, inheritance of membership and religion.Acculturation in the form of livelihood in the form of livelihood change, job change and cooperation among tribes. Changes in the system of the shift of the Dayak agricultural system from cultivation of dry field to wet field, changes in the work of the Javanese became better and can be rubber gardening, and inter-tribal cooperation on the activities pengarih or sambetan. Acculturation Language in the form of Javanese language blend Dayak people can speak Java and vice vers. Acculturation of Arts in the form of participation and enthusiasm of citizens towards Javanese arts (Kuda lumping) and the original art of Dayak tribe (Tari Perang)Keyword : Acculturation, Culture, Ethnic, Javanese, Dayak